Bromatological Analysis from Medicinally Relevant Wild Edible Plant Parts - Shivprasad, Mahadkar; Sujata, Valvi; Varsha, Jadhav (International Journal of Innovative Research in Medical Science, 2016)
The wild edible plant parts such as tubers, rhizomes, corm, fruits, inflorescence, leaves, flowers, stems were consumed by rural peoples of Kolhapur district, Maharashtra, India. Ten wild edible plant species viz. Bauhinia recemosa Lam., Caryota urens L, Gmelina arborea Roxb, Oroxylum indicum (L.) Vent, Zanthoxylum rhetsa (Roxb.) DC, Commelina benghalensis L, Garcinia indica (Du Petit-Thou.) Choisy, Smilax zeylanica L, Ensete superbum (Roxb.) Cheesuran, Woodfordia fruticosa (L.) Kurz. from different localities of Kolhapur district was selected for present study. In bromatological analysis leaves of Commelina benghalensis show lower dry matter (4.44±1.10 %FW) and crude fat (0.8± 0.3 %DW) content. Lower crude protein (1.375±0.0190 g/100g DW) and total ash (6.24±0.15% DW) content was observed in fruits of Bauhinia recemosa. Fruits of Gmelina arborea show higher moisture (94.2±1.25 %FW) and total ash (18.16±0.10%DW) but higher dry matter (37.9±±0.50%FW) and lower moisture (62.1±0.50 %FW) was observed in fruits of Caryota urens. Fruits of Zanthoxylum rhetsa consist of higher crude fat (3.8±0.45 %DW), crude protein (4.518±0.0184 g/100g DW) and lower crude fiber (6.23±0.55 %DW) content. Crude fiber (12.79±2.52 %DW) is higher in flowers of Ensete Superbum. In case of carbohydrate analysis highest reducing sugars, total sugars and energy was observed in flowers of Woodfordia fruticosa (0.4131±0.0058 g/100g DW, 0.8122 ±0.0071 g/100g DW, 48.4851±0.4893 kcal/100g DW ) and lowest in flowers of Ensete Superbum (0.0775±0.0052 g/100g DW, 0.1035±0.0129 g/100g DW, 18.3683±0.2240 kcal/100g DW), highest starch content was observed in flowers of Woodfordia fruticosa (2.0808±0.0327 g/100g DW) and lowest in fruits of Caryota urens (0.8772±0.0155 g/100g DW).